Game performance differences between winning and losing sitting volleyball teams regarding teams` ability - Marszalek, J.; Gómez, M.-A.; Molik, B. (International Journal of Performance Analysis in Sport, 2018)
Performance analysis research has tried to find those factors that best differentiate winning and losing teams in sport. However, the available research done within disabled sport is scarce. Then, the purpose of this study was to differentiate winning and losing teams of elite sitting volleyball games according to teams` ranking (best/worst teams). All the matches played by the sitting volleyball men`s teams (n = 16) during the World Sitting Volleyball Championships in 2014, were analysed 168 sets (50 matches). The indicators analysed were: attack, serve, block, block of serve, defence (overhead, forearm, others), and ball receiving (overhead, forearm, others). Game analyses were described by Modified Game Performance Sheet for Sitting Volleyball. The binomial logistic regression was used to differentiate winning and losing teams. The results showed that effectiveness of attack is the main factor that characterized winning teams. Effectiveness of attack and block as well as the number of all attempts of attack and serve increases the probability of winning the set in these games between best (first eight teams) and worst teams (last eight teams). The current findings allow coaches to better control and prepare competitions focusing on improving attack, serve and reception.